Topical issues of corruption counteraction - V. V. Sverchkov (Russian Journal of Economics and Law)
Objective: to give answers to the topical issues of corruption counteraction. Methods: the methodological basis of research is the overall dialectic method of cognition, as well as general scientific, special and private methods of research. Results: basing on the analysis and summarizing of results of investigative-court practice, legislation provisions and criminal law doctrine, the features of the following are shown а) defining the object and revealing the subjective signs of bribery; б) stating the fact of bribe extortion, promising/offering mediation in bribery. Scientific novelty: The answers have been found for the topical questions of corruption counteraction, for instance, at criminal-legal level - to establish property deprivation as a punishment and a means of criminal-procedural pressure. Practical value: The results of the carried out research can be used in scientific, law-making and law-enforcement activity, in the educational process of juridical universities and faculties.